3
$\begingroup$

I did the following:

$$\cos' x=-1/2 \\ -\sin x=-1/2 \\ \sin x = 1/2$$

So, I guess that in this case I have to find values such that $\sin x = 1/2$, these values are $\pi/5$ and $5\pi /6$ (I know that there are more values than these, those are just some values that do have these property). Generally, I'd have:

enter image description here

Now I can write:

$$y=mx+b\\ 1/2=\pi/5\cdot -1/2+b \\1/2+\pi/10=b\\\frac{5+\pi}{10}=b$$

Then:

$$y=-1/2x+\frac{5+\pi}{10}$$

But this line doesn't seems to be tangent to $y=\cos x$, see:

enter image description here

I may have done some silly mistake, but I can't find it.

$\endgroup$
  • $\begingroup$ First, you get two solutions $\pi/6$ and $5\pi/6$ modulo $2\pi$, why does it become $\pi/5$ and $5\pi/6$? $\endgroup$ – user37238 Apr 27 '15 at 10:55
  • 1
    $\begingroup$ Secondly, how do you go from $y=mx+b$ to the next line? Especially, how do you get the value $1/2$ on the left hand side? $\endgroup$ – user37238 Apr 27 '15 at 10:56
  • $\begingroup$ @user37238 When I evaluate $-\sin x=- 1/2$, I'd have the pair $(\pi/6,-1/2)$. The first item of the pair is $x$, the second one is $y$. I just made the substitution. $\endgroup$ – Billy Rubina Apr 27 '15 at 11:01
  • $\begingroup$ You're looking for a line tangent to the curve $y=\cos x$. You have found the points where the slope is $-1/2$. Now that you know the slope (at the point $x=\pi/6$) of the tangent line you need to find the value of the function ($\cos$) at this point to completely know the tangent line. $\endgroup$ – user37238 Apr 27 '15 at 11:08
  • $\begingroup$ @user37238 Yes! I guess you helped me to find the silly mistake. Let me write it. $\endgroup$ – Billy Rubina Apr 27 '15 at 11:12
1
$\begingroup$

Indeed the start is right. $$cos'x = {{-1}\over{2}} \\ sin(x) = {1 \over 2}$$ Giving you the condition which was asked. Solving for it gives you. $$x = (-1)^narcsin({1\over2}) + 2n\pi;\ n \ is\ integer \\ x = (-1)^n({\pi \over 6}) +2n\pi $$

Then if you wish to find the tangent line you should use $(y - y_0) = y' (x - x_0)$ Where $x_0$ is $(-1)^n({\pi \over 6}) +2n\pi$ and $y_0$ is $cos((-1)^n({\pi \over 6}) +2n\pi)$

You can also substitute y' = -1/2.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.